Optimalisasi kolaborasi mahasiswa dengan instansi praktik dalam menentukan minat praktik kerja perpustakaan - Evriza, Eka; Pramudibyanto, Hascaryo (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2023)
Purpose. The purpose of this study is to obtain a description of the collaboration carried out by students participating in Library Internship Programs with the institutions where they undergo their internships. Methodology. Using an online questionnaire as the instrument distributed to students participating in internships, responses were received from students from 127 provinces in Indonesia.Results and discussion. The information gathered indicates that library internship activities already reflect a diversity of interests, competencies, and objectives as part of the library internship experience. There is alignment between the activities carried out and various aspects of library management, collection development, and the complexity of seeking career opportunities in the library field. Conclusions. An analysis of the collaboration strategy between students and practical institutions in determining the type of library practice reveals several important aspects. Students must have a clear understanding of the learning objectives and library practice requirements through constructive dialogue with the practical institution. They also need to build a professional network and participate in activities that broaden their understanding of various types of practices. However, the lack of variety in the scope of practices suggests the need for guidance or alignment activities before the practical placement is carried out, allowing students to choose a practice type that aligns with their mentor's educational background.